Bhatt–Hauser Oxidation: A Site-Selective Late-Stage Benzylic C–H Oxidation - Ghosh, Ketaki; Mal, Dipakranjan (Synlett, 2025)
This account provides an overview of the copper-catalyzed, K2S2O8-mediated regioselective advanced-stage benzylic C–H oxidation, a process we have named as the Bhatt–Hauser oxidation. Its impact as a synthetic method, especially in the context of the total synthesis of natural products, is presented.1 Introduction2 The Bhatt–Hauser Oxidation3 Mechanism of the Bhatt–Hauser Oxidation4 Modifications of the Bhatt–Hauser Oxidation5 Synthesis of Formylanthraquinones and an Unprecedented Fragmentation6 General Applications7 Applications in the Total Synthesis of Natural Products: Advanced-Stage Oxidation8 Conclusion
Keywords: site-selective oxidation; regioselectivity; potassium perdisulfate; copper sulfate; total synthesis; natural products